2010
DOI: 10.1097/mop.0b013e32833a468e
|View full text |Cite
|
Sign up to set email alerts
|

Firm foundations: strength-based approaches to adolescent chronic disease

Abstract: Strength-based approaches, including motivational interviewing, hold tremendous potential for equipping providers to address the rapidly increasing burden of chronic disease in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…Several studies suggest the use of strength-based motivational interviewing and problem-solving to improve health literacy, motivation, and resilience in adolescents with chronic health conditions. 31,32 In addition, providers should work closely with parents to teach them skills in encouraging independent disease self-management in their children. Providers should also work closely with other providers to better coordinate care.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest the use of strength-based motivational interviewing and problem-solving to improve health literacy, motivation, and resilience in adolescents with chronic health conditions. 31,32 In addition, providers should work closely with parents to teach them skills in encouraging independent disease self-management in their children. Providers should also work closely with other providers to better coordinate care.…”
Section: Discussionmentioning
confidence: 99%
“…A 2013 study found that the 5 Cs PYD model could be applied to youth with COCI (Maslow & Chung). A few studies have examined outcomes associated with PYD programs for youth with COCI and found improvements in disease management, self-advocacy in the healthcare environment, leadership opportunities, and community membership (Chung, Burke, & Goodman, 2010;Maslow & Chung, 2013;Maslow et al, 2016).…”
Section: Positive Youth Development Frameworkmentioning
confidence: 99%
“…Peer mentoring, incorporated into many PYD programs, provides opportunities for social connection and may contribute to improved problem-solving abilities, better coping styles, leadership skill development, and increased self-esteem [57,61,62]. However, all peer group and mentoring programs have potential risks for participants, such as encountering new and unpleasant information about their illness, 'sick' group over-identification and stigmatization, and learning maladaptive coping mechanisms [61,62].…”
Section: Positive Youth Development (Pyd) and Peer Mentoringmentioning
confidence: 97%
“…One option for comprehensive transition preparation is PYD-a conceptual framework emphasizing development of intrinsic strengths and resilience with provision of extrinsic supports [57,58]. PYD programs foster life skills, acquisition of leadership abilities, and sustained caring adult-youth relationships and have been successfully used with 'at risk' youth [58][59][60].…”
Section: Positive Youth Development (Pyd) and Peer Mentoringmentioning
confidence: 99%